The complete mitochondrial genome sequence of Onychostoma barbatulus (Cypriniformes, Cyprinidae). (October 2014) - Li, Bin-jun; Cheng, Hui-Ling
Abstract The Onychostoma barbatulus is a small cyprinid fish and distributed mainly in Taiwan and mainland China. The total length of O. barbatulus mitogenome is 16, 597 bp, and had a gene content consisting of 13 protein-coding genes, 22 transfer RNAs, 2 ribosomal RNAs genes and a noncoding control region. The determination of O. barbatulus mitogenome would play an important role both in the delineation of phylogeographic history and population genetic structure, as well as reflection of conservation efforts on the genetic diversity and population vitality.